2010
DOI: 10.1364/ol.35.003970
|View full text |Cite
|
Sign up to set email alerts
|

Theory of fiber optic Raman polarizers

Abstract: We propose and apply a theoretical description of a Raman amplifier based on the vector model of randomly birefringent fibers to the characterization of Raman polarizers. The Raman polarizer is a special type of Raman amplifier with the property of producing a highly repolarized beam when fed by relatively weak and unpolarized light. [2,3]. The analytic theory of [2] is limited by the condition that the beat length L B is smaller than the birefringence correlation length L c , and therefore its validity is qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 5 publications
3
62
0
Order By: Relevance
“…Input temporal variations of the polarization of the signal beam disappear at the device output, where the signal SOP is strictly aligned along the (0, 1, 0) direction. As expected, the output signal SOP coincides with the SOP of the pump beam, see [4].…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Input temporal variations of the polarization of the signal beam disappear at the device output, where the signal SOP is strictly aligned along the (0, 1, 0) direction. As expected, the output signal SOP coincides with the SOP of the pump beam, see [4].…”
supporting
confidence: 82%
“…From the practical point of view, fiber optic Raman polarizers differ from typical Raman amplifiers in that a peculiar type of gain fiber should be selected. Namely, a Raman polarizer requires a low polarization mode dispersion (PMD) fiber, i.e., with PMD coefficients lower than 0.02 ps , see [1], [4], [5]. The lower the PMD coefficient, the greater the PDG, the better the performance of the Raman polarizer, the worse the RIN induced over the signal.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The new approach developed by Sergeyev et al [7,8] have shown that it is possible to simultaneously mitigate both PDG and PMD by using a fiber with a particular spin profile or, more specifically, a two-section fiber ('two-section approach') in which the first section has no spin and the second one is periodically spun. A new approach based on using anisotropy of Raman amplification (Raman polarizer) to repolarize and amplify signal rather than to depolarize it has been recently developed by Martinelli et al [9] , Kozlov et al [10] and Ursinini et al [11]. In this approach, arbitrary at the input, signal SOP with low input power is attracting to the pump SOP with high input power (polarization pulling) and so is stabilizing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%